Social Environment and Food and Beverage Intake in European Adolescents: The Helena Study. Issue 5 (4th July 2022) - Santaliestra-Pasías, Alba M.; Felez, Alicia Pérez; Huybrechts, Inge; Censi, Laura; González-Gross, Marcela; Forsner, Maria; Sjöström, Michael; Lambrinou, Christina P.; Amaro, Francisco; Kersting, Mathilde; Molnar, Denes; Kafatos, Anthony; et al.
Abstract: Background: The family environment influences food consumption and behaviours, which impact adolescent's eating habits, diet and health. Young individuals who frequently eat family meals are less likely to develop risk- and behaviour-related outcomes as obesity. Aim: To assess the relationship between the family meal environment and food and macronutrient consumption in European adolescents. Methods: 1, 703 adolescents aged 12.5-17.5 years (46.5% male) from the European HELENA cross-sectional study were selected. Sociodemographic variables and dietary intake using two non-consecutive self-reported 24-hour dietary recalls were collected from all the included participants. The relationship between family meals' environment and food and macronutrient consumption was analized using analysis of covariance. Results: Adolescents who used to take their main meals with their family were associated with high consumption of healthy foods and beverages (i.e. vegetables, fruit, milk, water) and low consumption of energy dense food and beverages as chocolate, savoury snacks, sugar or juices compared with those who used to eat alone, with friends or other people ( p  < 0.05). Conclusion: The company/people with whom adolescents consume their meal have an important influence on the adolescent's consumption of different types of food (especially at lunch). Family's environment during meals has been associated with a high consumption of healthy foods.